(para‐Cymene)Ru(II) Complexes with Chelating Benzotriazole Ligands: Application in Oxidation and Reduction Catalysis. Issue 2 (16th January 2020) - Pandey, Sharmila; Mandal, Tanmoy; Singh, Vivek
Abstract: 1‐Heteroaryl‐substituted benzotriazole motifs represent a new class of bidentate chelating ligands for several transition metals. Although metal complexes having such ligands in tris‐ and bis‐chelated binding have been extensively studied, investigation of mono‐chelated metal complexes, especially their structural and catalytic properties, is rarely explored. In this work, two such complexes – [( para ‐cymene)Ru(BTZ‐2P )Cl]PF6 and [( para ‐cymene)Ru(BTZ‐2Q )Cl]PF6, (BTZ‐2P =1‐(pyridine‐2‐yl)‐1H‐benzo[ d ][1, 2, 3]triazole; BTZ‐2Q =1‐(quinoline‐2‐yl)‐1H‐benzo[ d ][1, 2, 3]triazole) have been synthesized and characterized through various spectroscopic method and X‐ray crystallography. Their electronic spectra and electrochemical properties have also been explored. Both the complexes have been successfully applied in two types of important catalytic processes – (a) oxidation of aryl olefins to corresponding aromatic carbonyl compounds, and (b) transfer hydrogenation of aromatic carbonyl compounds to the corresponding alcohols. Abstract : Chelating bidentate coordination of benzotriazole‐based ligands was exploited to access half‐sandwich Ru(II) complexes, [( para ‐cymene)Ru(BTZ‐2P)Cl]PF6 and [( para ‐cymene)Ru(BTZ‐2Q)Cl]PF6, which were utilized in two types of catalytic processes – oxidation of alkenes and reduction of ketones.